Crops behind closed walls: Fortified storage at Castelinho in the Late Iron Age of NW Iberia. (April 2020) - Seabra, L.; Santos, F.; Vaz, F.C.; Leite, J.; Tereso, J.P.
Highlights: Iron Age monumental fortified storage facility, unique in Northwest Iberia. Elevated granaries mostly used to store naked wheat, broomcorn millet and barley. Access and redistribution of goods at the household level or controlled by specific elements of the community. Aggregation place where communities would be engaged in social interactions and power relations would be established. Abstract: The site of Castelinho (Torre de Moncorvo, northeast of Portugal) is a fortification strategically placed on a small elevation, near the river Sabor, built in the Late Iron Age and occupied until the Early Roman period. It is characterized by impressive defensive features, including large walls with turrets, ditches and complex entrances, inside of which no clear evidences of domestic areas were found. On the contrary, this monumental defensive apparatus seems to have served mostly to protect several storage facilities, mainly elevated granaries, in which abundant archaeobotanical remains were recovered. The excavation of Castelinho comprised the systematic sampling of sediment in a wide diversity of contexts, ultimately leading to the recovery of large amounts of charcoal, fruits and seeds. Most came from secondary or tertiary refuse deposits but some seem to have been actually related to the destruction of granaries by fire. Carpological results show the predominance of naked wheat ( Triticum aestivum/durum ) while hulled barley ( Hordeum vulgare ) and broomcorn millet ( Panicum miliaceum ) were found in smaller amounts. These crops were stored fully processed, taking into account the almost absence of chaff and the scarce presence of weeds. Charcoal analysis suggest Pinus pinaster and Quercus evergreen provided most of the wood used in the construction of the granaries. In this study, this data will be presented, discussed and compared with archaeobotanical and archaeological information from other sites excavated in the Sabor Valley and in the surrounding region. The size and monumentality of Castelinho, combined with the fact that it provided few evidences of other activities besides storage, suggests this site had a relevant role for local communities. This will be discussed together with other evidence of the social relevance of storage for Late Iron Age communities in the region.